KEMAMPUAN ANTAGONISTIK BEBERAPA ISOLAT Bacillus spp. TERHADAP PATOGEN Pyricularia oryzae PENYEBAB PENYAKIT BLAS TANAMAN PADI (Oryza sativa L.) PADA BEBERAPA KONSENTRASI - Setiawan Setiawan; Yenny Wuryandari; Tr Mujoko (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2025)
Rice (Oryza sativa L.) is a staple food crop that plays a vital role in supporting national food security. One of the major constraints in rice cultivation is blast disease, caused by the fungal pathogen Pyricularia oryzae, which can significantly reduce crop productivity and lead to substantial economic losses. The conventional management of this disease relies heavily on chemical pesticides, which pose long-term risks to environmental and human health. Therefore, eco-friendly alternatives such as biological control agents are necessary, with Bacillus spp. being one promising candidate. This study aimed to evaluate the antagonistic activity of three Bacillus spp. isolates (Bcz-14, Bcz-20, and Bcz-30) against P. oryzae at two bacterial population densities (10⁶ CFU/mL and 10⁹ CFU/mL) under in vitro conditions. The experiment was conducted at the Plant Health Laboratory, Faculty of Agriculture, Universitas Pembangunan Nasional “Veteran” East Java, from January to March 2025. Results of the antagonism assay demonstrated that all Bacillus spp. isolates inhibited the growth of P. oryzae, with the highest inhibition observed in treatments Bcz-14 and Bcz-30 at 10⁶ CFU/mL, with inhibition rates of 24.29% and 23.35%, respectively. The observed inhibition mechanisms included competition and antibiosis. Microscopic observations revealed abnormal hyphal structures in P. oryzae, including lysis, swelling, and chlamydospore formation, in response to Bacillus spp. treatment.